Persepsi Masyarakat dan Strategi Pengembangan Agrowisata Salak di Desa Sibetan Kecamatan Bebandem Kabupaten Karangasem Bali - Bachtiar, Anas Rizki; Windia, Wayan; Astiti, Wayan Sri (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 4 No 1 (2016), 2016)
Sibetan Village is one of Agrotourism place that could not give the significant result from its source. It makes a lag between the development of tourism object and its captivation from the farmers’ living. From this fact, a strategy is needed to develop agrotourism in Sibetan. The aim of this research is to know people’s perception about the development of agrotourism, the analysis of internal and eksternal environment, to create an alternative strategy and also the priority of how developing Salak Agrotourism. Data analysis in this research is using matrix internal-external (IE) analysis, matrix grand strategy, SWOT and followed by QSPM analysis to determine the strategy priority.  The result of this reasearch is (1) People’s perception in Sibetan about the development of agrotourism gets 86,86 %; (2) Identification of internal-external factor, accesibility of agrotourism, great panorama view, safety, another attraction from salak agrotourism as tourist’s destination, local government policy, organisation, the intention of world population of doing tourism with the development of technology; (3) alternatives strategy that is created based on SWOT is to increase people’s role in managing agrotourism, to cultivate its natural resource to optimize the excellence agrotourism, to maintain the quality of the products, to increase the promotion with technology, to develop a good relationship between government and companies, and also to increase the quality of human resource by held a training to develop a good skill in service; (4) the right strategy based on QSPM is to gain its own natural resource in increasing the excellence of agrotourism and also to keep the quality of the products.  Suggestion from this research is in order to make the local government of Karangasem regency Salak Agrotourism in Sibetan as the main priority to develop the tourism and gives support in the development of salak agrotourism activity. Besides, it needs a good cooperation between government and private or public companies in developing salak agrotourism.
Keywords: Agrotourism, People’s Perception, Strategy, SWOT